If $S_{n}$ denotes the sum of the cubes of the first $n$ natural numbers and $s_{n}$
denotes the sum of the first n natural numbers then find the value of $\sum_{k=1}^{n} \frac{S_{k}}{S_{k}}$
Given in the question, Sn denotes the sum of the cubes of the first n natural numbers.
sn denotes the sum of the first n natural numbers.
Note:
I. Sum of first n natural numbers, 1 + 2 +3+…n,
$\sum_{k=1}^{n} k=\frac{n(n+1)}{2}$
II. Sum of squares of first $n$ natural numbers, $1^{2}+2^{2}+3^{2}+\ldots n^{2}$,
$\sum_{k=1}^{n} k^{2}=\frac{n(n+1)(2 n+1)}{6}$
III. Sum of cubes of first $n$ natural numbers, $1^{3}+2^{3}+3^{3}+\ldots . n^{3}$,
$\sum_{k=1}^{n} k^{3}=\left(\frac{n(n+1)}{2}\right)^{2}$
IV. Sum of a constant k, N times,
$\sum_{k=1}^{N} k=N k$
So,
$\mathrm{S}_{\mathrm{n}}$ denotes the sum of the cubes of the first $\mathrm{n}$ natural numbers. (Given data in the question).
$S_{n}=\sum_{k=1}^{n} k^{3}=\left(\frac{n(n+1)}{2}\right)^{2}$
sn denotes the sum of the first n natural numbers.
$s_{n}=\sum_{k=1}^{n} k=\frac{n(n+1)}{2}$
$\frac{S_{k}}{S_{k}}=\frac{\left(\frac{k(k+1)}{2}\right)^{2}}{\frac{k(k+1)}{2}}=\frac{k(k+1)}{2}$
To determine the given ratio in the question,
$\sum_{k=1}^{n} \frac{S_{k}}{S_{k}}=\sum_{k=1}^{n} \frac{k(k+1)}{2}$
$=\frac{1}{2}\left[\sum_{k=1}^{n} k^{2}+\sum_{k=1}^{n} k\right]$
$=\frac{1}{2}\left[\left(\frac{n(n+1)(2 n+1)}{6}\right)+\left(\frac{n(n+1)}{2}\right)\right]$
$=\frac{n(n+1)}{4}\left[\left(\frac{(2 n+1)}{3}\right)+1\right]$
$=\frac{n(n+1)}{4}\left[\left(\frac{(2 n+4)}{3}\right)\right]$
$=\frac{n(n+1)(n+2)}{6}$
So, the value of $\sum_{k=1}^{n} \frac{s_{k}}{s_{k}}=\frac{n(n+1)(n+2)}{6}$